Isolated hemorrhage in the cerebellar vermis with vertigo and body lateropulsion to the contralesional side - Lee, Dong Hyun (Yeungnam Univ J Med, 2019)
There have been several reports of patients with isolated lesions of the cerebellar vermis presenting with clinical features similar to those of peripheral vestibulopathy. We report a case of small, isolated hematoma in the cerebellar vermis in a patient who presented with vertigo, ipsilesional nystagmus, and body lateropulsion to the contralesional side without the usual signs or symptoms of cerebellar dysfunction. Although they present with symptoms that mimic those of peripheral vestibulopathy, and brain computed tomography shows no abnormality, as there may be a small, isolated hematoma or infarction in the cerebellar vermis. Thus, brain magnetic resonance imaging should be performed in elderly patients with vascular risk factors.